Understanding HSRP using augmented reality (AR) / Siti Anisah Zarikhan - Zarikhan, Siti Anisah (2020)
Augmented reality is technology that is based on virtual reality. It presents information generated by the computer on the real world using a camera. This technology has the potential to draw students’ attention to visualize a layer of information on real objects using handheld mobile devices such as tablets and smartphones. The objective of this project is to design and develop the augmented reality application notes for Hot Standby Routing Protocol (HSRP). This application will be a tool for students to enhance their knowledge and motivation in learning about the HSRP protocol. The benefits of this AR application are the mobility of it as students can use the application anywhere and anytime, they wanted. Furthermore, this application prototype may lead to another prototype of AR application that may help students in learning more networking subjects.